2015
DOI: 10.1016/j.cognition.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

It is there whether you hear it or not: Syntactic representation of missing arguments

Abstract: Many languages allow arguments to be omitted when they are recoverable from the context, but how do people comprehend sentences with a missing argument? We contrast a syntactically-represented account whereby people postulate a syntactic representation for the missing argument, with a syntactically-non-represented account whereby people do not postulate any syntactic representation for it. We report two structural priming experiments in Mandarin Chinese that showed that comprehension of a dative sentence with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 65 publications
0
47
0
Order By: Relevance
“…These results replicated previous evidence for syntactic priming of dative structures in Mandarin (e.g., Cai et al, 2012), using a different paradigm. (Cai et al, 2011(Cai et al, , 2015, as in English (Bock, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results replicated previous evidence for syntactic priming of dative structures in Mandarin (e.g., Cai et al, 2012), using a different paradigm. (Cai et al, 2011(Cai et al, , 2015, as in English (Bock, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al (2012) replicated priming for PO/DO sentences, but also demonstrated priming of mappings both between thematic roles and grammatical relations, and between thematic roles and word order positions, demonstrating that semantic representations are accessed during sentence processing in Mandarin (as in other languages). Cai et al (2015) showed further that both PO and DO sentences with 'missing' arguments (e.g., PO sentence: Niuzai mai-le yiben shuhou song-le gei shuishou, 'cowboy buy LE a book later give LE to sailor', meaning 'The cowboy bought a book and later gave to the sailor') primed PO and DO sentences to the same extent as (full form) PO and DO prime sentences. Cai et al (2012) also showed that their results could not be explained in terms of differences in emphasis associated with the two structures (see Vernice et al, 2012).…”
Section: Using Structural Priming To Investigate Syntactic Representamentioning
confidence: 97%
See 1 more Smart Citation
“…According to syntactic accounts, the syntactic representation includes a PP (e.g., V NP PP), so that it is aligned with the semantic (but not the phonological) representation, as in Figure 2a; according to semantic accounts, it does not include a PP (e.g., V NP), so that it is aligned with the phonological (but not the semantic) representation, as in Figure 2b. Cai et al (2015) found that missing (elided) NP arguments in Mandarin are represented syntactically. They showed that full DO targets were primed by DOs in which the Theme was missing (e.g., Niuzai mai-le yiben shu hou song-gei-le shuishou; "The cowboy bought a book and later gave the sailor [the book]") to the same extent as by DOs in which the Theme was not missing (Niuzai mai-le yiben shu hou song-gei-le shuishou naben shu; "The cowboy bought a book and later gave the sailor the book").…”
Section: Syntactic Representationmentioning
confidence: 99%
“…The fillers, held constant across the three versions of the task, primed 24 sentences equally divided between two structures: transitives (k = 12) and reflexives (k = 12). These structures acted as distracters (see Cai, Pickering, Wang, & Branigan, 2015, for a similar design). Prime-target pairs were always separated by a filler trial and conditions alternated.…”
Section: Priming Taskmentioning
confidence: 99%